Metastatic adenocarcinoma of mandible: A case report - Kiran Kumar Kattappagari; Baddam Venkat Ramana Reddy; Joshua Elizabeth; Umadevi M Krishnamohan Rao; Kannan Ranganathan (Wolters Kluwer Medknow Publications, 2013)
Metastatic adenocarcinoma is a glandular tissue malignancy, which spreads to other regions of the body. Adenocarcinoma may develop anywhere in the body and commonly metastasizes to the jaw bone. We present a case of 83-year-old male, with a complaint of swelling on the lower left side of mandible. The clinical description of our case is supported by clinical, radiographic and pathological features.